Panama : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2001)
This report provides background information and supporting analyses for the staff report for the 2000 Article IV Consultation discussions with Panama. The paper presents an overview of economic developments since 1998. The study summarizes the financial and economic aspects of the operation of the Panama Canal, and discusses the economic impact of the reversion of the Canal and its adjacent areas to Panama. The paper also analyzes the progress of bank supervisory reform, and describes poverty and poverty alleviation programs.